2000
DOI: 10.1083/jcb.151.2.425
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain of Influenza Hemagglutinin Exhibits a Stringent Length Requirement to Support the Hemifusion to Fusion Transition

Abstract: Glycosylphosphatidylinositol-anchored influenza hemagglutinin (GPI-HA) mediates hemifusion, whereas chimeras with foreign transmembrane (TM) domains mediate full fusion. A possible explanation for these observations is that the TM domain must be a critical length in order for HA to promote full fusion. To test this hypothesis, we analyzed biochemical properties and fusion phenotypes of HA with alterations in its 27–amino acid TM domain. Our mutants included sequential 2–amino acid (Δ2–Δ14) and an 11–amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
191
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 63 publications
(101 reference statements)
7
191
2
Order By: Relevance
“…In the absence of fusion proteins, the process of bilayer fusion is a physical process with multiple high-energy intermediates (77,78) corresponding to: (i) diffusion of the membranes together, (ii) dehydration of the bilayers as the headgroups of opposing bilayers come into still closer proximity, (iii) formation of a lipidic stalk, (iv) hemifusion, (v) pore formation and expansion. Viral fusion proteins and SNARE proteins utilize essentially irreversible, energetically favorable conformational transitions to lower the activation energy for membrane fusion (50,51,77,78). Thus, they are active participants that shape the energy landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of fusion proteins, the process of bilayer fusion is a physical process with multiple high-energy intermediates (77,78) corresponding to: (i) diffusion of the membranes together, (ii) dehydration of the bilayers as the headgroups of opposing bilayers come into still closer proximity, (iii) formation of a lipidic stalk, (iv) hemifusion, (v) pore formation and expansion. Viral fusion proteins and SNARE proteins utilize essentially irreversible, energetically favorable conformational transitions to lower the activation energy for membrane fusion (50,51,77,78). Thus, they are active participants that shape the energy landscape.…”
Section: Discussionmentioning
confidence: 99%
“…If indeed FPs adopt a TM orientation, then one might envision a mechanism akin to SNARE proteins (50)(51)(52)(53), in which both the target and vesicular proteins have TM helices that associate as membrane fusion progresses. Accordingly, we investigate herein a class I fusogenic protein, F, from parainfluenza virus 5 (PIV5), which, like influenza virus HA and HIV gp41, has an N-terminal FP in the mature, cleaved protein (3).…”
mentioning
confidence: 99%
“…C9 and C45 are dispensable for receptor-triggered target membrane association, but they are stringently required for the lipid mixing stage of fusion. We envision two non-mutually exclusive roles for the cysteines flanking the EnvA fusion peptide: (i) to allow the EnvA TM subunit to fold back into a trimer of hairpins compact enough to mediate lipid mixing, perhaps involving interactions between the fusion loop and the pre-TM or TM regions (1,2,16,20) of EnvA or (ii) to allow the fusion peptide to remain tightly associated with the target membrane during the foldback stage of fusion. Our findings are likely relevant to structural requirements for other internal fusion peptides flanked by Cys residues, notably those of the Ebola virus and Marburg virus glycoproteins.…”
mentioning
confidence: 99%
“…Indeed, in the case of influenza virus, Judy White and coworkers have shown that the membrane-spanning domain exhibits a stringent length requirement to support the hemifusion to fusion transition [48]. Moreover, in the case of SIV, Eric Hunter and coworkers observed that progressive truncations C-terminal to the membrane-spanning domain of simian immunodeficiency virus Env reduce fusogenicity and increase concentration dependence of Env for fusion.…”
Section: Development Of Site-directed Photosensitized Labeling To Stumentioning
confidence: 99%